Annual cycle of export fluxes of biogenic matter near Hanna Shoal in the northeast Chukchi Sea. (July 2020) - Lalande, Catherine; Grebmeier, Jacqueline M.; Hopcroft, Russell R.; Danielson, Seth L.
Abstract: The Chukchi Ecosystem Observatory (CEO), a mooring array of subsurface oceanographic instruments, was established on the northeast Chukchi Sea continental shelf to obtain time-series measurements of physical, biogeochemical, and biological parameters. A sequential sediment trap was deployed on a CEO mooring 8 m above seafloor to measure export fluxes of chlorophyll a (chl a ), microalgal cells, zooplankton fecal pellets, total particulate matter (TPM), particulate organic carbon (POC), and zooplankton actively entering the trap from August 2015 to July 2016. These time-series measurements allowed us to monitor sympagic and pelagic algal production, the seasonal development of the zooplankton community, pelagic-benthic coupling, and particulate matter export in relation to snow and sea-ice cover on the shallow Chukchi Sea continental shelf. Notably, chl a and algal fluxes were nearly as high from August to October 2015 as in June–July 2016, indicating substantial autumn production. Autumn algal fluxes were dominated by the epipelic Cylindrotheca closterium while summer fluxes were dominated by pennate diatoms, including Fossula arctica and Neodenticula seminae . Peaks in the export of the exclusively sympagic diatom Nitzschia frigida in May and June 2016 indicated the release of ice algae due to snow and ice melt events. While pelagic copepods Calanus glacialis/marshallae, Pseudocalanus spp. and Oithona similis were the dominant copepods collected in the sediment trap, meroplanktonic stages of benthic organisms displayed the largest abundances and reflected mixing of pelagic stages and resuspension events on the shallow Chukchi Sea shelf. Enhanced fecal pellet carbon fluxes reflected zooplankton grazing in August and September 2015 and in July 2016. Despite the grazing pressure, high chl a, diatom and POC fluxes during these periods allowed strong pelagic-benthic coupling in the northeast Chukchi Sea. Persistent summer and autumn production also suggest that the local benthic community benefits from a sustained food supply rather than episodic flux events. Overall, these observations demonstrate the importance of year-round monitoring for fully understanding the phenology of marine processes and set a baseline for understanding the impact of environmental changes on Arctic marine ecosystems.